FORMS OF LAW ENFORCEMENT AND THEIR SPECIFIC FEATURES: A SOCIO-LEGAL ANALYSIS - Nazarova , Durdona (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Law enforcement is the most authoritative and complex mechanism of legal realization, representing the exclusive prerogative of the state to ensure compliance, resolve disputes, and apply sanctions. This empirical socio-legal study categorizes and evaluates the specific features of the two primary forms of state law enforcement: executive-operative (regulatory) and jurisdictional (law-protecting). A retrospective analysis of 150 formalized state enforcement acts, evenly distributed between administrative agencies and judicial bodies within the Tashkent region, was conducted to assess procedural efficiency and subjective citizen satisfaction. The findings demonstrate a significant structural dichotomy. Executive-operative enforcement, primarily handling licensing and social provisions, accounted for the majority of routine state legal interactions, showcasing a faster resolution time (averaging 14 days) and higher public satisfaction (78 out of 100 points). Conversely, jurisdictional enforcement, utilized for applying legal sanctions and resolving acute civil or criminal disputes, proved highly resource-intensive, requiring an average of 48 days for final resolution (p < 0.001) with significantly lower satisfaction indices due to its punitive nature. The study concludes that the modernization of the legal system must focus on expanding automated, digital mechanisms for executive-operative enforcement, thereby reducing the bureaucratic burden and reserving complex jurisdictional enforcement strictly for severe legal breaches and unresolvable disputes.